Fluticasone furoate nasal spray in the treatment of allergic rhinitis - Pedro Giavina-Bianchi; Rosana Agondi; Rafael Stelmach; Alberto Cukier; Jorge Kalil (Dove Medical Press, 2008)
Pedro Giavina-Bianchi1, Rosana Agondi1, Rafael Stelmach2, Alberto Cukier2, Jorge Kalil11Division of Clinical Immunology and Allergy, University of São Paulo, São Paulo, Brazil; 2Pulmonary Division, University of São Paulo, São Paulo, BrazilAbstract: Allergic rhinitis (AR) is a prevalent disease with great morbidity and significant societal and economic burden. Intranasal corticosteroids are recommended as first-line therapy for patients with moderate-to-severe disease, especially when nasal congestion is a major component of symptoms. To compare the efficacy and safety profile of different available intranasal corticosteroids for the treatment of AR, it is important to understand their different structures and pharmacokinetic and pharmacodynamic properties. Knowledge of these drugs has increased tremendously over the last decade. Studies have elucidated mechanisms of action, pharmacologic properties, and the clinical impact of these drugs in allergic respiratory diseases. Although the existing intranasal corticosteroids are already highly efficient, the introduction of further improved formulations with a better efficacy/safety profile is always desired. Fluticasone furoate nasal spray is a new topical corticosteroid, with enhanced-affinity and a unique side-actuated delivery device. As it has high topical potency and low potential for systemic effects, it is a good candidate for rhinitis treatment.Keywords: fluticasone furoate, corticosteroids, rhinitis, efficacy, safety, ARIA